Computers and games : 8th International Conference, CG 2013, Yokohama, Japan, August 13-15, 2013, Revised Selected Papers - Iida, Hiroyuki; Plaat, Aske; van den Herik, H. Jaap (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International Conference on Computers and Games, CG 2013, held in Yokohama, Japan, in August 2013, in conjunction with the 17th Computer and Games Tournament and the 20th World Computer-Chess Championship. The 21 papers presented were carefully reviewed and selected for inclusion in this book. They cover a wide range of topics which are grouped into five classes: Monte Carlo Tree Search and its enhancements; solving and searching; analysis of game characteristic; new approaches; and serious games.